Analysis of periarticular bone changes in patients with cutaneous psoriasis without associated psoriatic arthritis - Simon, Dominic; Faustini, F.; Englbrecht, Matthias; Kleyer, Arnd; Kocijan, R.; Haschka, Judith; Finzel, Stephanie; Kraus, Sebastian; Hueber, Axel; Sticherling, Michael; Schett, Georg; Rech, J. (Annals of the Rheumatic Diseases, 2016)
To search for structural bone changes in the joints of psoriasis patients without psoriatic arthritis (PsA).55 psoriasis patients without any current or past symptoms of arthritis or enthesitis and 47 healthy controls were examined by high-resolution peripheral quantitative CT scans of the metacarpophalangeal joints. Number, size and exact localisation of erosions and enthesiophytes were recorded by analysing axial scans of the metacarpal heads and phalangeal bases and were confirmed in additional coronal and/or sagittal sections. In addition, we collected demographic and clinical data including subtype, duration and severity of psoriasis.Psoriasis patients showed a larger and significantly increased number of enthesiophytes (total number 306; mean±SD/patient 5.62±3.30) compared with healthy controls (total number 138; mean±SD/patient 3.04±1.81, p<0.001). Enthesiophytes were typically found at the dorsal and palmar sides of the metacarpal heads where functional entheses related to extensor and flexor tendons are localised. Bone erosions were rare and not significantly different between psoriasis patients and healthy controls. If present, erosions were almost exclusively found at the radial side of the second metacarpal head in both psoriasis patients and healthy controls.Psoriasis patients without PsA show substantial signs of enthesiophyte formation compared with healthy controls. These changes represent new bone formation at mechanically exposed sites of the joint and substantiate the concept of the existence of a 'Deep Koebner Phenomenon' at enthesial sites in psoriasis patients.
EVALuna2:13130

Galectin-3 as a novel regulator of osteoblast-osteoclast interaction and bone homeostasis - Simon, Dominic; Derer, Anja; Andes, Fabian T.; Lezuo, Patrick; Bozec, Aline; Schett, Georg; Herrmann, Martin; Harre, Ulrike (Bone, 2017)
Bone tissue undergoes permanent and lifelong remodeling with a concerted action of bone-building osteoblasts and bone-resorbing osteoclasts. A precise cooperation between those two cell types is critical in the complex process of bone renewal. Galectin-3 is a member of the ?-galactoside-binding lectin family playing multiple roles in cell growth, differentiation and aggregation. As it has been described to be expressed in bone, galectin-3 might influence bone homeostasis by regulating the function and/or interplay of osteoblasts and osteoclasts. Here, we investigated the role of galectin-3 in osteoclastogenesis and osteoblast-osteoclast interactions. Bone histomorphometric analysis and ?CT measurements revealed a decreased trabecular bone volume and an increased osteoclast number in 12weeks old male galectin-3 knockout mice compared to wildtype littermates. Galectin-3 deficient bone marrow cells displayed a higher osteoclastogenic capacity in ex vivo differentiation assays, associated with elevated TRAF6 mRNA levels, suggesting an intrinsic inhibition of osteoclastogenesis by galectin-3 interfering with RANKL-mediated signaling. Furthermore, the addition of extracellular galectin-3 to murine or human osteoclastogenesis assays inhibited osteoclast formation and osteoclast numbers were higher in co-culture assays with galectin-3 deficient osteoblasts. In conclusion, our data suggest the secretion of galectin-3 as a novel mechanism for osteoblasts to control osteoclastogenesis and to maintain trabecular bone homeostasis independently of the RANKL/OPG-axis.
EVALuna2:13345

High prevalence of tenosynovial inflammation before onset of rheumatoid arthritis and its link to progression to RA-A combined MRI/CT study - Kleyer, Arnd; Krieter, Manuel; Oliveira, Isabelle; Faustini, Francesca; Simon, Dominic; Kämmerer, Nadine; Cavalcante, Alan; Tabosa, Taiane; Rech, Juergen; Hueber, Axel; Schett, Georg (Seminars in Arthritis and Rheumatism, 2016)
To define the anatomic distribution of the earliest inflammatory and structural changes in individuals with anti-citrullinated protein antibody (ACPA+) positivity but no signs of arthritis.ACPA+ individuals (N = 20) and healthy controls (N = 13) received simultaneous gadolinium-enhanced magnetic resonance imaging (MRI) and high-resolution peripheral quantitative computed tomography (HR-pQCT) of the hands. MRI sequences were scored for synovitis, osteitis, and bone erosions according to the RAMRIS method as well as for presence, localization, and extent of tenosynovitis. Bone erosions were validated by HR-pQCT scanning and related to the inflammatory changes found in the MRI.Tenosynovitis was the most prevalent inflammatory pathology, affecting 80% of ACPA+ individuals but none of the controls. Tenosynovitis at two or more anatomical sites was associated with later development of RA. Synovitis (65%) and osteitis (35%) were present in ACPA+ individuals as well, but at a lower frequency than tenosynovitis. MRI bone erosions were found in 65% of the individuals and additionally confirmed by HR-pQCT. Presence of MRI osteitis was the inflammatory pathology most strongly associated with bone erosions.Tenosynovitis is highly prevalent in ACPA+ individuals without arthritis and associated with later development of RA. Small erosions, often linked to osteitis, are also found in ACPA+ individuals without arthritis.
EVALuna2:13297

Methods for segmentation of rheumatoid arthritis bone erosions in high-resolution peripheral quantitative computed tomography (HR-pQCT) - Figueiredo, Camille P.; Kleyer, Arnd; Simon, Dominic; Stemmler, Fabian; d'Oliveira, Isabelle; Weißenfels, Anja; Museyko, Oleg; Friedberger, Andreas; Hueber, Axel; Haschka, Judith; Englbrecht, Matthias; Pereira, Rosa M.R.; et al. (Seminars in Arthritis and Rheumatism, 2017)
The comparison between different techniques to quantify the 3-dimensional size of inflammatory bone erosions in rheumatoid arthritis(RA) patients.Anti-cyclic citrullinated peptide antibody(ACPA) positive RA patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the metacarpophalangeal joints (MCP). Erosions were measured by three different segmentation techniques: (1) manual method with calculation by half-ellipsoid formula, (2) semi-automated modified Evaluation Script for Erosions (mESE), and (3) semi-automated Medical Image Analysis Framework (MIAF) software. Bland & Altman plots were used to describe agreement between methods. Furthermore, shape of erosions was classified as regular or irregular and then compared to the sphericity obtained by MIAF.A total of 76 erosions from 65 RA patients (46 females/19 males), median age 57 years, median disease duration 6.1 years and median disease activity score 28 of 2.8 units were analyzed. While mESE and MIAF showed good agreement in the measurement of erosion size, the manual method with calculation by half-ellipsoid formula underestimated erosions size, particularly with larger erosions. Accurate segmentation is particularly important in larger erosions, which are irregularly shaped. In all three segmentation techniques irregular erosions were larger in size than regular erosions (MIAF: 19.7 vs. 3.4mm(3); mESE: 15.5 vs. 2.3mm(3); manual = 7.2 vs. 1.52mm(3); all p < 0.001). In accordance, sphericity of erosions measured by MIAF significantly decreased with their size (p < 0.001).MIAF and mESE allow segmentation of inflammatory bone erosions in RA patients with excellent inter reader reliability. They allow calculating erosion volume independent of erosion shape and therefore provide an attractive tool to quantify structural damage in individual joints of RA patients.
EVALuna2:13514

Subclinical joint inflammation in patients with psoriasis without concomitant psoriatic arthritis: a cross-sectional and longitudinal analysis - Faustini, Francesca; Simon, Dominic; Oliveira, Isabelle; Kleyer, Arnd; Haschka, Judith; Englbrecht, Matthias; Cavalcante, Alan Rodrigues; Kraus, Sebastian; Tabosa, Taiane Ponte; Figueiredo, Camille; Hueber, Axel; Kocijan, Roland; et al. (Annals of the Rheumatic Diseases, 2016)
To search for subclinical inflammatory joint disease in patients with psoriasis without psoriatic arthritis (PsA), and to determine whether such changes are associated with the later development of PsA.Eighty-five subjects without arthritis (55 with psoriasis and 30 healthy controls) received high field MRI of the hand. MRI scans were scored for synovitis, osteitis, tenosynovitis and periarticular inflammation according to the PsAMRIS method. Patients with psoriasis additionally received complete clinical investigation, high-resolution peripheral quantitative CT for detecting erosions and enthesiophytes and were followed up for at least 1 year for the development of PsA.47% of patients with psoriasis showed at least one inflammatory lesion on MRI. Synovitis was the most prevalent inflammatory lesion (38%), while osteitis (11%), tenosynovitis (4%) and periarticular inflammation (4%) were less frequent. The mean (±SD) PsAMRIS synovitis score was 3.0±2.5 units. Enthesiophytes and bone erosions were not different between patients with psoriasis with or without inflammatory MRI changes. The risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia, but only 13% if patients had normal MRIs and did not report arthralgia.Prevalence of subclinical inflammatory lesions is high in patients with cutaneous psoriasis. Arthralgia in conjunction with MRI synovitis constitutes a high-risk constellation for the development of PsA.
EVALuna2:13265